2012
DOI: 10.1186/2046-2395-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine extends life span, improves healthspan, and delays age-associated pathology in Caenorhabditis elegans

Abstract: BackgroundThe longevity of an organism is influenced by both genetic and environmental factors. With respect to genetic factors, a significant effort is being made to identify pharmacological agents that extend life span by targeting pathways with a defined role in the aging process. On the environmental side, the molecular mechanisms responsible for the positive influence of interventions such as dietary restriction are being explored. The environment experienced by humans in modern societies already contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 66 publications
3
55
2
Order By: Relevance
“…They measured healthspan by monitoring worm movement, eating, and stress resistance over time. This is in contrast to prior studies which have reported improvements in nematode healthspan resulting from the same and other longevity-enhancing interventions (Johnson et al 2000;Herndon et al 2002;Huang et al 2004;Kaeberlein et al 2006;Mehta et al 2009;Sutphin et al 2012). A major challenge for these types of studies in nematodes is that healthspan (and health itself) is difficult to define in worms, and each lab uses their own, somewhat arbitrary, healthspan measurements.…”
contrasting
confidence: 48%
“…They measured healthspan by monitoring worm movement, eating, and stress resistance over time. This is in contrast to prior studies which have reported improvements in nematode healthspan resulting from the same and other longevity-enhancing interventions (Johnson et al 2000;Herndon et al 2002;Huang et al 2004;Kaeberlein et al 2006;Mehta et al 2009;Sutphin et al 2012). A major challenge for these types of studies in nematodes is that healthspan (and health itself) is difficult to define in worms, and each lab uses their own, somewhat arbitrary, healthspan measurements.…”
contrasting
confidence: 48%
“…The efficacy of many longevity interventions is strongly dependent on environmental temperature (Lakowski & Hekimi, 1996; Gems et al ., 1998; Lee & Kenyon, 2009; Leiser et al ., 2011; Sutphin et al ., 2012; Horikawa et al ., 2015; Zhang et al ., 2015). To capture genes that influence longevity across the temperature spectrum, we employed a two‐temperature screening strategy, measuring lifespan of wild‐type (N2) worms subjected to RNAi targeting each gene at 15 and 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has detailed the role of temperature in specific aging interventions, such as reduced insulin signaling (Gems et al ., 1998), reduced hypoxic signaling (Leiser et al ., 2011), caffeine supplementation (Sutphin et al ., 2012), or disruption of physiological ‘clock’ genes (Lakowski & Hekimi, 1996), among others. Lee & Kenyon (2009) and Horikawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…1 supports the assertion that the types of research advocated above have barely begun. Kudos can be given to such scientists as Monica Driscoll (Onken and Driscoll, 2010), Matt Kaeberlein (Sutphin et al, 2012), Barry Halliwell (Ng et al, 2014), Heidi Tissenbaum (Bansal et al, 2015), Coleen Murphy (Hahm et al, 2015), Malene Hansen (Gelino et al, 2016) and others for having pioneered healthspan research in C. elegans . Let us hope we can see a similar expansion of such research in other model organisms, certainly to include mammalian models (Richardson et al, 2016).…”
Section: A Call For More Research On Genetic and Environmental Infmentioning
confidence: 99%